The impact of replacing wheat flour with cellular legume powder on starch bioaccessibility, glycaemic response and bread roll quality: A double-blind randomised controlled trial in healthy participants. (May 2021) - Bajka, Balazs H.; Pinto, Ana M.; Ahn-Jarvis, Jennifer; Ryden, Peter; Perez-Moral, Natalia; van der Schoot, Alice; Stocchi, Costanza; Bland, Catherine; Berry, Sarah E.; Ellis, Peter R.; Edwards, Cathrina H.
Abstract: The global rise in obesity and type 2 diabetes has generated significant interest in regulating the glycaemic impact of staple foods. Wheat breads (white or wholemeal) are popular staples, but have a high-glycaemic index, due to the highly digestible wheat starch. Reducing the glycaemic potency of white bread is challenging because the bread-making conditions are mostly conducive to starch gelatinisation. Cellular legume powders are a new source of type 1 resistant starch, where the starch is encapsulated by dietary fibre in the form of intact plant cell walls. The starch in these cell powders is less susceptible to gelatinisation and digestion than starch in conventional legume flours. However, legume cell resilience to baking conditions and the effects of this ingredient on glycaemic responses and product quality are unknown. Here we show that the integrity of cell wall fibre in chickpea powder was preserved on baking and this led to a 40% reduction in in vivo glycaemic responses (iAUC120 ) to white bread rolls ( 50 g available carbohydrate and 12 g wheat protein per serving) when 30% or 60% (w/w) of the wheat flour was replaced with intact cell powder. Significant reductions in glycaemic responses were achieved without adverse effects on bread texture, appearance or palatability. Starch digestibility analysis and microscopy confirmed the importance of cell integrity in attenuating glycaemic responses. Alternative processing methods that preserve cell integrity are a new, promising way to provide healthier low glycaemic staple foods; we anticipate that this will improve dietary options for diabetes care. Graphical abstract: Image 1 Highlights: Intact cell powder (ICP): a new legume ingredient increased type 1 resistant starch in bread rolls. ICP lowered starch bioaccessibility and glycaemic response of wheat bread rolls. Legume cell integrity was retained after baking and digestion. Wheat breads incorporating ICP had acceptable quality attributes.